بناء وتقنين مقياس العجز المتعلم للاعبي مراكز رعاية الموهبة الرياضية لكرة القدم - الفرطوسي علي سموم; شلال عباس علي; الحمیدي علي حمد سمیر (Journal of Sport Science Technology and Physical Activities, 2020)
The study aimed to build and standardize the learning disability scale to identify the level of players of football talent care centers.The researchers adopted a descriptive research methodology for football talented players in the talent care centers in the Ministry of Youth and Sports and the Amo Baba School School season (2018-2019), ages (15-17) years of total (185) players were all selected by (100%), and divided into three samples according to the requirements of the study (building 91 players) and exploratory (10 players) and (84 applications) and the areas were identified and drafted paragraphs sequentially According to the determinants of measurement and evaluation and extraction of the foundations and scientific transactions Building on her sample, tested a sample application on reconnaissance, and then applied to the sample application for the purposes of rationing, It was then applied to the sample application for rationing purposes, and the data were processed by SPSS program. Football players have the conditions to accept psychometric measuring instruments, and the players do not have a high level of learning talent. Or the Ministry of Youth and Sports, or the availability of specialist psychological counselor in the care of sports talent in football